THE ANALYSIS OF CONCEPTUAL APPROACHES TO THE RESOURCES OF COMMERCIAL BANKS - Yu.A. Toyirov (Scholar Express Journals, 2023)
This article contains the results of the analysis of conceptual approaches to the formation of resources and structural structure of commercial banks. In addition, the author's approach to the economic nature of the resources of commercial banks is reflected in the work
Keywords: resource; economic resources; commercial banks; bank resources